Educational Needs of Foreign Secondary Students and its Impediment in Malaysia: Teacher’s Perspective - Muslima Karawani; Suhailah Binti Hussien (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2020)
The enrollment of the international students in secondary schoo education in Malaysia has increased significantly in the last few years. This qualitative study involved the observation of the international students’ skills by their teacher in terms of academic and socio-cultural obstacles. The method of data collection employed was face to face semistructured interviews. Findings showed that international students experienced academic obstacles, challenges, cultural modification and social isolation. Academic obstacles and challenges that they faced include communication with teacher and classmates. Therefore, international students should be helped with their problem of social isolation by involving them in various group activities. Culturally, international students had to adjust to the different methods of thinking and learning in Malaysia. In order to overcome these challenges, students have to accept the resources and assistance from the teacher.